The Relationship Between Job Satisfaction and Job Performance Among Midwives Working in Healthcare Centers of Mashhad, Iran - Zahra Hadizadeh Talasaz; Shahla Nourani Saadoldin; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2014)
Background and Aim: Job satisfaction represents individuals' positive or negative attitude towards their occupation. Job satisfaction is of high significance in health care field and could affects the quality of patients' health care and satisfaction. Every organization should pay considerable attention to job satisfaction and performance and continually monitor these indices. Therefore, we aimed to determine the relationship between job satisfaction and job performance of midwives, employed in health care centers of Mashhad, Iran. Methods: This descriptive correlational study was performed on 90 midwives, working in healthcare centers of Mashhad, Iran, in 2014 who were selected through multistage sampling from five healthcare centers. Data collection tools included a questionnaire to record demographic, personal and occupational data, Minnesota Job Satisfaction Questionnaire (MSQ) as well as a self-structured observational checklist to measure the quality of educational, care, and communicative job performance of midwives. SPSS version 19 was used to analyze data through descriptive statistics, and also Spearman and Kruskal-Wallis tests. Results: The mean age of the participants was 39.63±6.92 years. Spearman correlation test showed a direct correlation between job satisfaction and the total score of job performance (P